2016
DOI: 10.1039/c6ra07176g
|View full text |Cite
|
Sign up to set email alerts
|

On the origins of the elasticity of cellulose nanofiber nanocomposites and nanopapers: a micromechanical approach

Abstract: The elastic properties of cellulose nanofibril (NFC) nanocomposites and nanopapers are predicted by a multiscale network model that shows that the deformation mechanisms are governed by the bonds between rigid NFC segments and in the kinked regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 86 publications
1
7
0
1
Order By: Relevance
“…Upon bending, the crystal developed a sharp kink identical to that observed experimentally for processed celluloses (Kekaelaeinen et al 2012;Wang et al 2012;Zeng et al 2012;Martoia et al 2016). We found shear deformations are very important when the bending load is applied on the hydrophobic face, for which the bending rigidity is also the lowest.…”
Section: Introductionsupporting
confidence: 55%
“…Upon bending, the crystal developed a sharp kink identical to that observed experimentally for processed celluloses (Kekaelaeinen et al 2012;Wang et al 2012;Zeng et al 2012;Martoia et al 2016). We found shear deformations are very important when the bending load is applied on the hydrophobic face, for which the bending rigidity is also the lowest.…”
Section: Introductionsupporting
confidence: 55%
“…Using volume excluded concepts, the authors showed that C* probably corresponded to a percolation threshold below which nanocellulose networks were no longer connected and lost their mechanical integrity. The percolation threshold that corresponds to a critical number of bonds or interactions per nanofibre z * , was estimated using the statistical tube model for fibrous networks of homogeneously distributed straight fibres [150][151][152]:…”
Section: Nanofibre Slendernessmentioning
confidence: 99%
“…Vast research efforts are currently underway worldwide to extract from biomass slender crystalline cellulose nanoparticles (CNs) ( 2 ), i.e., portions of microfibrils. CNs are used as building blocks for novel engineered materials, such as nanocomposites ( 2 , 3 , 5 ), densely packed nanopapers ( 6 9 ) and filaments ( 10 , 11 ) with tunable supermolecular nanostructures ( 12 , 13 ), and aerogels and foams ( 14 16 ). However, during extraction, processing, and use, CNs are subjected to complex stress environments that alter their morphology and mechanical properties.…”
mentioning
confidence: 99%